2010
DOI: 10.1159/000264632
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Loss of Basic Activities of Daily Living in Alzheimer Patients: A Cross-Sectional Study of the French REAL Cohort

Abstract: Background/Aims: To characterize loss of basic activities of daily living (BADL) in 687 Alzheimer’s disease (AD) community-dwelling patients included in the French REAL cohort. Methods: Patients had mild to moderately severe AD, and the mean age was 77.8 years. Patterns of loss of the 6 BADL were described at inclusion using the Lawton scale. Results: With 6 binary BADL scores, each patient presented at inclusion a set of losses. For 53% of women, the sets of losses were included within each other or were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…Furthermore, this result suggests that vital functions assessed by BI and VI decline earlier than eating ability. The data from specific groups of AD in the present study are in agreement with previous reports that referred to empirically supported strategies for feeding patients with dementia 3,8,12 …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Furthermore, this result suggests that vital functions assessed by BI and VI decline earlier than eating ability. The data from specific groups of AD in the present study are in agreement with previous reports that referred to empirically supported strategies for feeding patients with dementia 3,8,12 …”
Section: Discussionsupporting
confidence: 93%
“…In addition, we found that the presence of dysphagia signs significantly contributed to the decrease in independence in eating. This is in agreement with some clinical reports that showed that dysphagia is the most common factor in advanced AD 3,8,12 . At the time when dysphagia becomes evident in AD, worsening of the severity of dementia, impairment of the basic physical functions, 33 such as the defense reflexes, 4 and pseudobulbar paralysis 37 are usually present.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Basic ADL (b-ADL), which includes personal hygiene, dressing, and eating, remain stable the longest [27]. Only in major NCD does one need the support of others in performing b-ADL [23,28,29]. Consequently, assessment of ADL is paramount to determine the degree of impairment in everyday functioning and to underpin accurate diagnostic classification in NCD [9,12,15,30].…”
Section: Introductionmentioning
confidence: 99%